f(x)=(e^x)(ax^2+x+1)求导,结果是e^x(ax^2+x+1+2ax+1),
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 11:13:15
f(x)=(e^x)(ax^2+x+1)求导,结果是e^x(ax^2+x+1+2ax+1),f(x)=(e^x)(ax^2+x+1)求导,结果是e^x(ax^2+x+1+2ax+1),f(x)=(e^
f(x)=(e^x)(ax^2+x+1)求导,结果是e^x(ax^2+x+1+2ax+1),
f(x)=(e^x)(ax^2+x+1)求导,结果是e^x(ax^2+x+1+2ax+1),
f(x)=(e^x)(ax^2+x+1)求导,结果是e^x(ax^2+x+1+2ax+1),
f(x)=(e^x)(ax^2+x+1)
f`(x)=e^x(ax^2+x+1)+e^x(2ax+1)
=e^x(ax^2+x+2ax+2)
怎样对f(x)=e^x/1 ax^2进行求导,过程要分析清楚。 F’(x)=[(e^x)’(1 ax^2)-( e^x)(1 ax^2)’]/(1 ax^2)^2 =[e^x(1 ax^2
f(x)=(e^x)(ax^2+x+1)求导,结果是e^x(ax^2+x+1+2ax+1),
F(x)=e^(2x+1)-ax+1
f(x)=[(1+x)/(1-x)]e^(-ax)求导
函数f(x)={ax^2+1,x≥0;(a^2-1)e^ax,x
f(x)=e^x/1+ax^2 求导 后面是-2ax还是-ax
已知x=1是函数f(x)=(x^2+ax)e^x,x>0和bx ,x
已知f(x)=(ax+1)*e^x的导数
f(x)=e^ax/x-1求导.
f(X)=x^2e^ax(a
f(X)=e^ax/x-2单调区间
f(x)=x^2e^ax的导数,
f(x)=e^x+ax^2+bx 当f(1)=e f’(1)=e求a b
f(x)=x^2e^x-1+ax^3+bx^2求导是什么?
f(x)=e^x (x^2+ax+1)的导数
已知函数f(x)={ax2+1,x≥0 (a+2)e^ax,x
讨论f(x)=e^x(ax^2+x+1)的单调性
讨论f(x)=e^x(x^2+ax+1)的单调性
f(x)=(x^2+ax+b)e^x (x属于R),g(x)=|f(x)|/e^x,且g(x)=|f(x)|/e^x在[-1,1]上的最大值是M,证明M>=1/2